2008
DOI: 10.1364/ao.47.000944
|View full text |Cite
|
Sign up to set email alerts
|

Side-line tunable laser transmitter for differential absorption lidar measurements of CO_2: design and application to atmospheric measurements

Abstract: A 2 microm wavelength, 90 mJ, 5 Hz pulsed Ho laser is described with wavelength control to precisely tune and lock the wavelength at a desired offset up to 2.9 GHz from the center of a CO(2) absorption line. Once detuned from the line center the laser wavelength is actively locked to keep the wavelength within 1.9 MHz standard deviation about the setpoint. This wavelength control allows optimization of the optical depth for a differential absorption lidar (DIAL) measuring atmospheric CO(2) concentrations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 12 publications
2
72
0
Order By: Relevance
“…For comparison with other frequency-stabilized lasers in the 2.05-μm wavelength range reported in the literature, we have also calculated a root-mean-square (rms) standard deviation of ~190 kHz for our frequency-stabilized laser over a period of more than 3 h. Koch et al reported an rms deviation of 870 kHz for a cw solid-state laser frequency-stabilized around 1.2 GHz away from the center of a CO 2 absorption line at 2053 nm [13], whereas Refaat et al achieved an rms deviation of 650 kHz for a semiconductor laser stabilized to the center of the CO 2 R(30) transition at 2051 nm, as estimated from a statistical analysis and a fitting procedure [14]. One should notice in these comparisons that different measurement instrumentation and data processing were used in each case to retrieve the frequency instability.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…For comparison with other frequency-stabilized lasers in the 2.05-μm wavelength range reported in the literature, we have also calculated a root-mean-square (rms) standard deviation of ~190 kHz for our frequency-stabilized laser over a period of more than 3 h. Koch et al reported an rms deviation of 870 kHz for a cw solid-state laser frequency-stabilized around 1.2 GHz away from the center of a CO 2 absorption line at 2053 nm [13], whereas Refaat et al achieved an rms deviation of 650 kHz for a semiconductor laser stabilized to the center of the CO 2 R(30) transition at 2051 nm, as estimated from a statistical analysis and a fitting procedure [14]. One should notice in these comparisons that different measurement instrumentation and data processing were used in each case to retrieve the frequency instability.…”
Section: Discussionmentioning
confidence: 78%
“…The VCO frequency (here set around 1 GHz) was measured with a frequency counter, after frequency division by a factor 20 and down-conversion with a mixer to be in the operation range of the counter Fig. 13 Frequency stability (Allan deviation) of the laser locked with a detuning of ~1 GHz from the center of the CO 2 R(30) transition using the developed modulation sideband locking scheme locked conditions, by analyzing the heterodyne beat signal with the frequency comb using a frequency discriminator [30]. Results are displayed in Fig.…”
Section: Laser Stabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the wavelength accuracy and stability, a master wavelength reference against a sample of CO2 in a gas cell is established. One of the CW lasers, called the center-line reference, is locked on the center of the CO2 absorption line R(30) by a frequency modulation spectroscopic technique [4]. A second laser, called the tunable side-line, is referenced to the center-line laser by a heterodyne technique.…”
Section: Fig 1 2-micron Co2 Ipda Instrument Block Diagrammentioning
confidence: 99%